2015
DOI: 10.1007/s13187-015-0898-9
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Cervical Cancer Screening in Burkina Faso: Needs for Patient and Professional Education

Abstract: Background Cervical cancer is among the leading causes of cancer deaths for women in low-income African countries, such as Burkina Faso. Given that cervical cancer is a preventable disease through early detection and vaccination, this study aimed at understanding the barriers to cervical cancer early detection in Ouagadougou, the capital city of Burkina Faso. Women seeking screening and treatment for cervical cancer (n=351) during the period of May-August 2014, at the Yalgado Ouedraogo University Hospital were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 30 publications
(36 reference statements)
6
32
1
6
Order By: Relevance
“…Evidence from low and middle income countries has shown that low individual socio-economic status influences health outcomes through a lack of awareness about the health impact of lifestyle risk factors and reduced access to healthcare for financial reasons (27)(28)(29). Our study showed that women who reported monthly household income less than or equal to 66 USD were more likely to have a precancerous cervical lesion compared to those who reported an income of more than 66 USD.…”
Section: Discussionmentioning
confidence: 54%
“…Evidence from low and middle income countries has shown that low individual socio-economic status influences health outcomes through a lack of awareness about the health impact of lifestyle risk factors and reduced access to healthcare for financial reasons (27)(28)(29). Our study showed that women who reported monthly household income less than or equal to 66 USD were more likely to have a precancerous cervical lesion compared to those who reported an income of more than 66 USD.…”
Section: Discussionmentioning
confidence: 54%
“…Similar findings have been documented elsewhere. [9,12] Further barriers of significant concern are erroneous cultural beliefs that cervical cancer is not among the diseases that require orthodox medical intervention, and the high preference given to the use of herbs in the management of most diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Earlier studies attributed poor screening uptake to the presence of competing healthcare priorities, burdens of diseases other than cancers, and reduced public budgets resulting in failure to establish cervical cancer screening programmes. [9] In Nigeria, healthcare services have traditionally been based on curative interventions rather than preventive healthcare. War and civil strife have had consequences on the existing healthcare infrastructure.…”
mentioning
confidence: 99%
“…Although no formal definition for SES or life-course SES exists, education-based SES measures have emerged as stronger predictors of screening compared with employment-based measures. This suggests that factors related to literacy, awareness of the benefits of screening, low self-efficacy regarding cancer prevention and early detection options may be more important for health outcomes, including cancer screening,26 29 compared with income and financial factors 44. This is supported by our observation, as well as other studies showing a stronger influence of maternal education on cancer screening and daughter's adult health,43 45 that may be due to the fact that women may be strongly socialised and view their mothers as role models compared with their fathers.…”
Section: Discussionmentioning
confidence: 99%